Produtividade da mão de obra na execução de alvenaria estrutural em edifício residencial - Muller, Hyago Maurício Bremm; Rodegheri, Priscila Mirapalhete; Paliari, José Carlos (SIMPÓSIO BRASILEIRO DE GESTÃO E ECONOMIA DA CONSTRUÇÃO, 2021)
The search for improvements in the construction industry has made companies better know their production processes in order to reduce consumption of material and activity that do not add value to the product, as well as ensure better productivity of their teams. For these reasons, this research sought to measure, through a case study, indicators of labor productivity in the execution of the structural masonry of a residential building located in the city of São Carlos, SP, run by a small company. The results showed that the studied team has a higher productivity when compared to the indicators provided by the Sinapi and TCPO tables. In the analysis of time distribution, we observed significantly low unproductive activity and values ​​of good and productive activity and compatible with values ​​presented in the literature. Although it has occurred in a short period of time, this study enlightened that small businesses have optimized their processes in order to remain competitive in the marketplace, demonstrating the efficiency of their team.